Social policy and practice in Canada : a history - Finkel, Alvin, 1949- (Wilfrid Laurier University Press, 2006)
Traces the history of social policy in Canada from the period of First Nations' control to the present day, exploring the various ways in which residents of the area known today as Canada have organised themselves to deal with (or to ignore) the needs of the ill, the poor, the elderly, and the young. This book is the first synthesis on social policy in Canada to provide a critical perspective on the evolution of social policy in the country. While earlier work has treated each new social program as a major advance, and reacted with shock to neoliberalism's attack on social programs, Alvin Finkel demonstrates that right-wing and left-wing forces have always battled to shape social policy in Canada. He argues that the notion of a welfare state consensus in the period after 1945 is misleading, and that the social programs developed before the neoliberal counteroffensive were far less radical than they are sometimes depicted. Social Policy and Practice in Canada: A History begins by exploring the non-state mechanisms employed by First Nations to insure the well-being of their members.; It then deals with the role of the Church in New France and of voluntary organisations in British North America in helping the unfortunate. After examining why voluntary organisation gradually gave way to state-controlled programs, the book assesses the evolution of social policy in Canada in a variety of areas, including health, treatment of the elderly, childcare, housing, and poverty.